(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
In this article we will propose the "Intelligent Artificial Clerk" which is an Intelligent Agent designed to assist users, editors, facilitators of interactive meetings and rapporteurs in general, and in particular the clerks of the High Court of Kananga in order to save them from heavy tasks related to the reproduction of official documents, in particular minutes during hearings and public hearings. Apart from this task, this intelligent agent will also allow the court to be seized remotely and will transmit interviews and trials in audio format via Mp3 files.